Patient-centred care: The patients' perspective - A mixed-methods pilot study - Roseanne E. Turner; Elize Archer (AOSIS, 2020)
Background: Patient centredness is a broad concept, a moral philosophy. Patient-centred care can be viewed as the actions of patient-centredness. One of the most pertinent actions that a healthcare practitioner can utilise to deliver patient-centred care is empathic communication. Whilst many medical programmes include empathetic communication skills as part of their curricula, the recipients of this care are not asked about the relevance of this teaching. Aim: We attempted to determine whether the Western constructs of empathy were relevant in our context and also establish whether there were any parts of the medical interview which participants felt were especially important to be communicated to in their home language. Setting: Two urban communities within the City of Cape Town, Western Cape Province, South Africa. Methods: This was a mixed-methods pilot study using an explanatory sequential design. Participants who would typically make use of public health care facilities and whose first language was Afrikaans or isiXhosa were conveniently sampled. A subgroup of participants was invited to take part in a follow-up focus group discussion to add clarity to the survey responses. Results and Conclusion: Western constructs for empathy appeared to be relevant within our multicultural context. Patients wanted to communicate with their doctors and understand the cause of their problems as well as the management plan. Finally, whilst the numbers in this pilot study were too small to be generalisable, it was evident that patient-centred care was not perceived to be implemented in some public healthcare facilities attended by the participants, which resulted in them feeling unseen and disrespected.